Monitoring the condition of hydroponic growing media based on internet of things - Zakia Rahman, Agil; Aswardi; Hendri (Journal of Industrial Automation and Electrical Engineering, 2025)
Manual hydroponic techniques still make it difficult for farmers to control nutrients accurately, so new innovations are needed to make it easier for farmers to farm with hydroponic methods. This study aims to develop hydroponic farming using internet of things technology. This study was conducted using an experimental method. With this method, researchers took some data such as volume, temperature nutrients and water pH and then compared them with actual values. The author also took some component stress measurement data and then compared it with the component datasheet to determine the condition and suitability of the component. The research object used is celery plants. The test results prove that the development of monitoring and control technology for hydroponic planting media has been successfully carried out. Testing proves that the system can automatically control nutrients and pH and monitor the condition of the planting media at the same time. When nutrients are added, the pH of the water decreases because the graph of increasing nutrients is inversely proportional to the decrease in water pH. When the pH of the water decreases, the motor automatically turns on to increase the pH to the ideal value. Thus, farmers can more easily control the nutrients in the planting media.